1984
DOI: 10.1093/jn/114.9.1541
|View full text |Cite
|
Sign up to set email alerts
|

Portal and Vena Caval Plasma Methionine Concentrations in Young Pigs Administered L-Methionine, N-Acetyl-L-Methionine and N-Acetyl-D-Methionine

Abstract: N-Acyl-methionine derivatives have been proposed as replacements for methionine in supplementing food products low in this amino acid. We studied the effects of N-acetyl-L-methionine, N-acetyl-D-methionine and L-methionine loads (2 mmol/kg body weight) on portal and vena caval plasma amino acid concentrations in young pigs (n = 4). L-Methionine loading significantly increased mean (+/- SD) portal and vena caval plasma methionine concentrations from baseline values of 6.44 +/- 1.03 and 6.63 +/- 0.99 mumol/100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Increases in NAM were not detected at 30 min in either sex, suggesting that NAM was rapidly excreted or further metabolized. Daabees et al (1984) reported similar Met levels in pigs dosed with Met or NAM, consistent with efficient conversion of NAM to Met.…”
Section: Resultssupporting
confidence: 54%
“…Increases in NAM were not detected at 30 min in either sex, suggesting that NAM was rapidly excreted or further metabolized. Daabees et al (1984) reported similar Met levels in pigs dosed with Met or NAM, consistent with efficient conversion of NAM to Met.…”
Section: Resultssupporting
confidence: 54%
“…NALM fed to adult humans appears to be equivalent to dietary L-methionine (25). Similar findings are reported in adult pigs (27), rats (28), and human infants; the metabolic requirements of the latter for L-methionine and NALM appear to be greater than those of adults (29). In mice, greater body weight gains are achieved with NALM, as well as some other methionine derivatives, than with L-methionine (30).…”
Section: Discussionsupporting
confidence: 69%
“…The amino acid content in hepatic portal venous plasma increases shortly after intrajejunal administration [3], however, such a rapid increase of the l-arginine plasma level may be unusual after oral administration. The functional significance of the effect of l-arginine therefore remains to be elucidated in future studies.…”
Section: Discussionmentioning
confidence: 96%